Energy Conversion Environmentaly Friendly Solutions To The Global Energy Crisis - zaki, kaka ibnu; Nugraha, Firza Wahyu; Saputra, Ryan Dhania Hanafi; Darmawan, Yogi Dwi; Mutaqin, Moh Zainul; Yulianto, Fahmi Naufal (JMEL : Journal of Mechanical Engineering Learning, 2025)
The global energy crisis has become one of the major challenges facing the world today. The increasing demand for energy, limited fossil fuel resources, and negative environmental impacts are driving the need to seek sustainable and environmentally friendly energy solutions. Renewable energy conversion, such as solar, wind, hydroelectric, biomass, and geothermal, offers great potential as an alternative source of clean and renewable energy. This is literature review studdy. This article explores the important role of renewable energy conversion in addressing the global energy crisis and mitigating climate change. By analyzing the technology, policies, economic, social, and environmental aspects related to renewable energy conversion, this article highlights environmentally friendly solutions that can support a sustainable energy transition and ensure future energy security. Furthermore, this article discusses the challenges and opportunities in integrating renewable energy into the energy system, as well as the importance of public participation and co-ownership models in renewable energy projects.